2003
DOI: 10.17660/actahortic.2003.597.42
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Callus Production and Glycosidal Content of Leaf Tissue Culture of Digitalis Lanata Ehrh.

Abstract: Grecian Foxglove, Digitalis lanata Ehrh. (Scrophulariaceae), is a perennial or biennial plant, which is a major source of digoxin and digitoxin. Its leaves are used for the preparation of these cardiac active glycosides for the treatment of cardio vascular disorders. This study was built on a suggestion that in Digitalis the explanted cells already contain all the genetic information that is required for the manufacture of digitoxin and digoxin. Accordingly, this genetic information will be present in callus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…As it turned out from our investigations, but also from the works of other authors (Ali & Iqbal, 2012;Bosila et al, 2003;Burbulis et al, 2007;Fatima et al, 2009;Polanco et al, 1988;Verma et al, 2016), the qualities of the callus obtained in in vitro culture (texture, colour, speed of cell proliferation, content in certain substances, etc. ), its subsequent evolution, biomass production, etc., depend on many factors, such as: the species, the genotype of the plant, the type of explant, its age, the composition of the nutrient medium, the growth regulators present in the culture medium (the type, concentration and ratio between them, in vitro cultivation conditions (light/dark, photoperiod, light quality and intensity, temperature) etc.…”
Section: Ocimum Basilicum -Primary Internode Callussupporting
confidence: 77%
“…As it turned out from our investigations, but also from the works of other authors (Ali & Iqbal, 2012;Bosila et al, 2003;Burbulis et al, 2007;Fatima et al, 2009;Polanco et al, 1988;Verma et al, 2016), the qualities of the callus obtained in in vitro culture (texture, colour, speed of cell proliferation, content in certain substances, etc. ), its subsequent evolution, biomass production, etc., depend on many factors, such as: the species, the genotype of the plant, the type of explant, its age, the composition of the nutrient medium, the growth regulators present in the culture medium (the type, concentration and ratio between them, in vitro cultivation conditions (light/dark, photoperiod, light quality and intensity, temperature) etc.…”
Section: Ocimum Basilicum -Primary Internode Callussupporting
confidence: 77%
“…These results reveal to the importance of BA levels and undifferentiated callus on digoxin and digitoxin contents. Whereas, in pervious study on Digitalis lanata (Bosila 2001), undifferentiated callus was recorded the low amount of digoxin and digitoxin contents (‹14 ng/g.D.W) in this concern, the result closely consist with Vela et al, (1991) on Digitalis plant, they found that, digoxigenen derivative were found in all clonally-prpagated plants, but the amount of these glycosides was much higher in those obtained from axillary buds. ………….…”
Section: Effect Of Ba Concentrations On Shoot Growth and Digoxin Contentmentioning
confidence: 85%
“…The potential of plant tissue culture for plant propagation and production of secondary metabolites has itself provided substantial for researcher (Dicosmo et al, 1995). In previous study, it was examined the effect of certain growth regulators, carbon sources, some major and minor-elements of MS basal medium used, and precursor of the cardenolide biosynthesis (Bosila, 2001). The overall vision of this research is to meet the needs and demands of important plant-derived pharmaceuticals by using plant tissue culture.…”
Section: Introductionmentioning
confidence: 99%